Basis Existence of Internal n-Graph Space - Lazwardi, Ahmad (CAUCHY, 2020)
Graph of real valued continuous function with special addition and multiplication has already proven that is isomorphic to real number system. Furthermore, the graph of continous real valued function forms a field. The aim of this research was to generalize such concept to its n-tuple Cartesian Product and to prove that interchange of basis still able to be executed. The result of this research is n-tuple Cartesian Product of graph function forms a vector space over Â and interchange of basis still able to be executed